2011
DOI: 10.3109/14767058.2011.572202
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of magnesium sulfate treatment on fetal brain in experimental intrauterine ischemia reperfusion injury

Abstract: We have shown that magnesium sulfate decreases TBARS levels significantly in fetal rat brain subjected to ischemia reperfusion injury and may have potential therapeutic benefits by reducing oxidative stress after intrauterine ischemia-reperfusion-induced fetal brain damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The protective efficacy of magnesium in permanent as well as in transient ischemia varies widely among the different studies reported. Thus, magnesium has been demonstrated to have protective effects in some animal models of brain damage in neonates (Mami et al,2006; Spandou et al,2007; Solaroglu et al,2011). Magnesium sulfate has also been shown to decrease the magnitude of the lesions in other animal models of focal hypoxic–ischemic and excytotoxic brain lesions (Marret et al,2007; Kang et al,2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective efficacy of magnesium in permanent as well as in transient ischemia varies widely among the different studies reported. Thus, magnesium has been demonstrated to have protective effects in some animal models of brain damage in neonates (Mami et al,2006; Spandou et al,2007; Solaroglu et al,2011). Magnesium sulfate has also been shown to decrease the magnitude of the lesions in other animal models of focal hypoxic–ischemic and excytotoxic brain lesions (Marret et al,2007; Kang et al,2011).…”
Section: Discussionmentioning
confidence: 99%
“…These paradoxical perspectives regarding the neuroprotective effect of MgSO 4 administration could be the consequence of variability in study design, depending on the dose and the experimental model, making it difficult to compare the outcomes directly. Studies with newborn rodents and different magnesium doses presented divergent results, including neuroprotection (Zhu et al, 2005;Spandou et al, 2007;Pazaiti et al, 2009;Cetinkaya et al, 2010;Solaroglu et al, 2011;Kang et al, 2011) or its absence (Greenwood et al, 2000;Gee et al, 2004;Zhu et al, 2004;Westermaier et al, 2005;Kalincik and Maresova, 2005;Dribben et al, 2009). On the other hand, although lamb or pig models are closer to humans (Yager, 2004), to date there are few studies on the protective effect of MgSO 4 administration in these newborn mammals suffering neonatal HI encephalopathy.…”
mentioning
confidence: 99%
“…In addition, MgSO4 pretreatment was able to reduce hypoxia effects in genes related to cell cycle, mitochondrial activity, cell death and neurogenesis in cerebellum (Haramati et al, 2010) and has also shown beneficial effects on the brain injury and body weight 72 h after severe maternal hypoxia (Hallak et al, 2000). MgSO 4 , used as a preventive treatment, has anti‐oxidant properties in a model of maternal hypoxia by reducing free radicals overproduction in term fetuses brains of guinea pigs (Maulik et al, 1999), and decreases lipid peroxidation 30 min after reperfusion following bilateral occlusion of utero‐ovarian arteries in rats (Solaroglu et al, 2011). In a similar model, maternal MgSO 4 treatment associated to dexamethasone reduced lipid peroxidation and mitochondrial damage induced by transient occlusion of utero‐ovarian arteries 60 min after reperfusion (Hasturk et al, 2013).…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…These paradoxical perspectives regarding the neuroprotective effect of MgSO 4 administration could be the consequence of the variability in the study design, depending on the dose and the experimental model, making it difficult to compare the outcomes directly. Studies with newborn rodents and different magnesium doses presented divergent results, including neuroprotection [125,126,127,128,129,130] or its absence [115,131,132,133,134,135]. On the other hand, although lamb or pig models are closer to humans [136], up to date there are few studies on the protective effect of MgSO 4 administration in these newborn mammals suffering neonatal HI encephalopathy [114].…”
Section: Pharmacological Therapiesmentioning
confidence: 99%